The Role of Location and The Convenience of Tourist Attractions on the Intention to Revisit Religious Tourist Attractions in Bekasi - UNTARI, Dhian Tyas; Khasanah, Fata Nidaul; Fakhrudin, Fakhrudin; Antariksa, Basuki; Wismayanti, Yanuar Farida; Satria, Budi; Nurmanto, David (Revista de turism - studii și cercetări în turism, 2025)
This study aims to analyze the effect of location and convenience of tourist attractions on the intention to revisit religious tourist attractions in Bekasi. A strategic location and convenient facilities are believed to play an important role in influencing tourists' decision to revisit. The research method used in this study is a quantitative approach with multiple regression techniques. Data was collected through questionnaires distributed to 200 respondents who had visited religious tourist attractions in Bekasi more than once. The analysis results show that both location and convenience significantly affect the intention to revisit. The regression coefficient for location is 0.42 (p < 0.01), while for convenience it is 0.54 (p < 0.01). This study concludes that both a strategic location and the convenience of facilities at religious tourist attractions in Bekasi can increase tourists' intention to revisit. Based on these findings, it is recommended that tourist attraction managers improve the accessibility of locations and the quality of facilities to enhance the visitors' experience and attract more tourists to return